Phosphoproteomic analysis identifies activated MET-axis PI3K/AKT and MAPK/ERK in lapatinib-resistant cancer cell line - Lee, Yong Yook (Nature Publishing Group, 2013)
Lapatinib, a dual inhibitor of epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) tyrosine kinases, has shown promising results as a growth inhibitor of HER2-positive cancer cells in vitro. However, similar to other EGFR-targeting drugs, acquired resistance to lapatinib by HER2-positive cancer cells remains a major clinical challenge. To elucidate resistance mechanisms to EGFR/HER2-targeting agents, we performed a systematic quantitative comparison of the phosphoproteome of lapatinib-resistant (LR) human gastric cancer cells (SNU216-LR) versus parental cells (SNU216) using a titanium dioxide (TiO(2)) phosphopeptide enrichment method and analysis with a Q-Exactive hybrid quadrupole-Orbitrap mass spectrometer. Biological network analysis of differentially expressed phosphoproteins revealed apparent constitutive activation of the MET-axis phosphatidylinositide 3-kinase (PI3K)/α-serine/threonine-protein kinase (AKT) and mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) signaling pathways in SNU216-LR. Inhibition of the PI3K/AKT and MAPK/ERK signaling pathways in SNU216-LR also leads to cell cycle arrest, confirming the biological network analysis. Lapatinib sensitivity was restored when cells were treated with several molecular targeting agents in combination with lapatinib. Thus, by integrating phosphoproteomic data, protein networks and effects of signaling pathway modulation on cell proliferation, we found that SNU216-LR maintains constitutive activation of the PI3K/AKT and MAPK/ERK pathways in a MET-dependent manner. These findings suggest that pathway activation is a key compensatory intracellular phospho-signaling event that may govern gastric cancer cell resistance to drug treatment.